Respuesta :
Translating:
Please help
I believe you want me to factor it, so:
( x + 1/2 )^2 + ( a - 2 )^2 - 14/2
Answer:
[tex]x=a+1,\:x=-a-3[/tex]
Step-by-step explanation:
Remove parenthesis:
[tex]x^2+2x-a^2-4a-3=0[/tex]
[tex]x_{1,\:2}=\frac{-2\pm \sqrt{2^2-4\cdot \:1\cdot \left(-a^2-4a-3\right)}}{2\cdot \:1}[/tex]
[tex]x_{1,\:2}=\frac{-2\pm \:2\left(a+2\right)}{2\cdot \:1}[/tex]
[tex]x_1=\frac{-2+2\left(a+2\right)}{2\cdot \:1},\:x_2=\frac{-2-2\left(a+2\right)}{2\cdot \:1}[/tex]
[tex]\mathrm{The\:solutions\:to\:the\:quadratic\:equation\:are:}[/tex]
[tex]x=a+1,\:x=-a-3[/tex]